Ti3C2Tx (MXene)/Pt nanoparticle electrode for the accurate detection of DA coexisting with AA and UA. Issue 11 (2nd March 2022) - Xue, You; Zheng, Yapeng; Wang, Enhui; Yang, Tao; Wang, Hongyang; Hou, Xinmei
Abstract : AA has an interfering effect on the electrochemical detection of DA. This interference rule was effectively used as a tool for accurate detection of DA levels in human body. Abstract : Dopamine (DA), uric acid (UA) and ascorbic acid (AA) are biomolecules widely distributed in the human body and play an important role in many physiological processes. An abnormal concentration of them is associated with various diseases. Thus, the accurate and fast detection of them has been one of the major demands in the healthcare industry. In this study, we demonstrate that Ti3 C2 T x /PtNP modified glassy carbon electrodes (GCEs) show a good electrochemical performance in the detection of DA and UA. However, there is no response signal to AA for either the CV or DPV curve due to the electrostatic repulsion between the negatively charged electrode surface and the negatively charged AA. Ti3 C2 T x (MXene)/Pt nanoparticles (PtNPs) are prepared by etching Ti3 AlC2 (MAX) with HF and reducing H2 PtCl6 with a NaBH4 aqueous solution. The morphology of Ti3 C2 T x /PtNPs is multilayered accordion-like Ti3 C2 T x decorated with PtNPs with a diameter of 10–20 nm. Furthermore, it is found that the electrochemical detection of DA will be enhanced by AA. The electrochemical detection rule of AA enhanced DA can be expressed as follows: I (DA+AA) = 0.011216 C AA + 0.039950 C DA + 1.1175( I (DA+AA) is the peak current of DA coexisting with AA. C AA is the concentration of AA. C DA is the concentration of DA). This can be used as a calibration to correct the concentration of DA when AA and DA coexist. Notably, AA promotes the stability of the electrode because it cleans the oxidation products from the electrode surface in time. In addition, the sensor exhibits good reproducibility and satisfactory recovery results in a real sample.